PENEGAKAN HUKUM TERHADAP PENGEMUDI YANG MEROKOK SAAT MENGENDARAI KENDARAAN BERMOTOR BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KOTA PEKANBARU - Yuliani Hutabarat; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
According to Law of the Republic of Indonesia No. 22 of 2009 on Traffic and Road Transport Article 283 reads "Any person who drives a Motor Vehicle on the Road unnaturally and performs other activities or is affected by a situation resulting in impaired concentration in driving on the Road as referred to in Article 106 paragraph (1) shall be convicted with a maximum imprisonment of 3 (three) months or a maximum fine of Rp750,000 ,00 (seven hundred and fifty thousand rupiah) The Criminal Sanction stipulated in the Regulation of the Minister of Transportation of the Republic of Indonesia No. 12 of 2019 Article 6C on the Protection of The Safety of Motorcycle Users Used for the Benefit of the Public reads: "Drivers are prohibited from smoking and conducting other activities that interfere with concentration while riding a motorcycle" but in its implementation there are still many drivers who smoke while riding a motor vehicle escape scrutiny from the police.The purpose of this study is to know the enforcement of the law against drivers who smoke while driving a motor vehicle, the barriers in law enforcement against drivers who smoke while driving a motor vehicle, what efforts can be made to overcome obstacles in law enforcement against drivers who smoke under Law No. 22 of 2009 On Traffic and Road Transport in Pekanbaru City Jurisdiction. The study was conducted at Satlantas Polresta Pekanbaru, while the population and samples were all parties related to the problems studied in this study, the data sources used, primary data, secondary data, and tertiary data, data collection techniques in this study were conducted with questionnaires, interviews, and literature studies.Enforcement of drivers who smoke while driving a motor vehicle is still low and needs to be enforced through the implementation of traffic regulations properly, the exemplary of law enforcement's own compliance, the straightforward stance of law enforcement, the adjustment of traffic rules on smoking prohibition while driving a motor vehicle. Advice for this issue Law enforcement against drivers who smoke while driving a motor vehicle so that it can be maximized considering the consequences inflicted if smoking while driving can interfere with concentration because having to drive with one hand, as well as the ash of the cigarette is also dangerous for other motorists if exposed to the eye will cause irritation so that it triggers a traffic accident.Keywords: Law Enforcement - Driver - Smoking